2017
DOI: 10.18393/ejss.293157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphorus solubilizing bacteria on some soil properties, wheat yield and nutrient contents

Abstract: Application of chemical fertilizers besides economic concerns has been a reason of environmental and ecosystem degradation, so sustainable organic agriculture is becoming popular in researches and among farming communities. Phosphorus holds second position after nitrogen among macronutrients required for better plant growth and is needed in higher amounts. Meeting this high phosphorus input for better crop yields causes environmental problems like eutrophication, so phosphorus solubilizing bacteria (PSB) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…Results of Attia and Abd El-Salam, 2016 emphasized that biofertilization is not a substitute but a partial supplement or the recommended NPK mineral fertilizers which could be ascribed partially to the increased mobility of fixed nutrients like P in the soil or fixing more N which reflected directly on most growth and yield characters of wheat in sandy soils. were results are in harmony with previous findings of Namvar and Khandan, 2013;Namli et al 2017;Karimi and Marashi, 2017;Khalilzadeh et al, 2018 andSingh et al, 2018.…”
Section: Effect Of Fertilizer Treatmentssupporting
confidence: 92%
See 1 more Smart Citation
“…Results of Attia and Abd El-Salam, 2016 emphasized that biofertilization is not a substitute but a partial supplement or the recommended NPK mineral fertilizers which could be ascribed partially to the increased mobility of fixed nutrients like P in the soil or fixing more N which reflected directly on most growth and yield characters of wheat in sandy soils. were results are in harmony with previous findings of Namvar and Khandan, 2013;Namli et al 2017;Karimi and Marashi, 2017;Khalilzadeh et al, 2018 andSingh et al, 2018.…”
Section: Effect Of Fertilizer Treatmentssupporting
confidence: 92%
“…They can play significant role in fixing atmospheric N and production of plant growth promoting substances (Attia and Abd El Salam, 2016). Many studies had addressed the advantageous effects of bacterial inoculation on plant physiology and growth of wheat (Singh et al, 2018, Namli et al, 2017and Khalilzadeh et al, 2018. The inoculation with bio-fertilization had significant effect on plant height, grain weight spike -1 , number of spikes m -2 , number of grains spike -1 , 1000grain weight, grain, straw and biological yields in wheat plants (Namvar and Khandan, 2013 as well as Karimi and Marashi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similar increases in absorption of the macronutrients include nitrogen and phosphorus have been reported in the host plant after inoculation of wheat grain by S. marcescens [62]. These observations have also been confirmed by [63] [64].…”
Section: Test In Greenhouse Conditionsupporting
confidence: 77%
“…Soil pH was affected by the fertilization treatments, decreasing significantly when the microbial fertilizer was applied at increasing rates, probably due to the presence of the Acidithiobacillus oxidizing bacteria, which metabolically produces sulfuric acid, whose acidity increases the release of P and K from rocks. Some authors agree that the addition of microorganisms for P and K solubilization reduce soil pH and, in some conditions, may release organic acids (Namli et al, 2017). Stamford et al (2007Stamford et al ( , 2009Stamford et al ( , 2015, for example, observed a reduction in soil pH when sulfur inoculated with Acidithiobacillus was applied to a soil of the Brazilian semiarid region.…”
Section: Resultsmentioning
confidence: 99%